Differential Expression and Localisation of Acetyl-Glucosamine, Acetyl-Galactosamine, Galactose, Mannose and Glucose Specific Lectins in Lingual Tonsil of Buffalo (Bubalus bubalis) - Kumar, Pawan (Journal of Buffalo Science, 2023)
The present study is the most comprehensive representation of lectin binding sites in various structural components of the lingual tonsil of six adult healthy buffaloes. The study was useful in determining the specific binding affinities of sixteen lectins of the N-acetylglucosamine group, i.e., Triticum vulgaris (WGA), succinylated Triticum vulgaris (s-WGA), Lycopersicon esculentum (LEL), Datura stramonium (DSL), Solanum tuberosum (STL); N-acetylgalactosamine group, i.e., Glycine max (SBA), Dolichos biflorus (DBA), Ricinus communis (RCA), Vicia villosa agglutinin (VVL); galactose group i. e Griffonia simplicifolia isolectin B4 (GS1B4), Arachis hypogaea (PNA), Artocarpus integrifolia (Jacalin), Erythrina crisa-galli (ECL); and glucose/mannose group i.e. Canavalia ensiformis (Con A), Lens culinaris agglutinin (LCA), Pisum sativum agglutinin (PSA) at structures of the lingual tonsil. The stratum spinosum of stratified squamous epithelium and modified reticular epithelium was strongly demarcated by lectins of the N-acetylglucosamine group. In addition, VVL, jacalin, and Con A lectins also showed strong responses for the same layer. The RCA, PNA, Con A, and PSA were the best markers for the collagen fibers of the subepithelial connective tissue. The lymphoid cells of the inter- and parafollicular region possessed receptors for ECL, WGA, and Con A. In contrast, the germinal center B cells were labeled only by the lectins of the glucose/mannose group. The mucosal secretions and the endothelium of the blood vessels were predominantly composed of glucosamine, sialic acid, and galactosamine sugars. The characteristic localization of lectins suggests the presence of specific receptor sites that may be useful for studying early disease pathogenesis and developing oral vaccines. In addition, the study will provide a database for comparing histochemical changes in different disease states.